Revealing the Mechanisms of Synergistic Action of Two Magainin Antimicrobial Peptides - Bechinger, Burkhard; Juhl, Dennis Wilkens; Glattard, Elise; Aisenbrey, Christopher (Frontiers in Medical Technology, 2020)
The study of peptide-lipid and peptide-peptide interactions as well as their topology and dynamics using biophysical and structural approaches have changed our view how antimicrobial peptides work and function. It has become obvious that both the peptides and the lipids arrange in soft supramolecular arrangements which are highly dynamic and able to change and mutually adapt their conformation, membrane penetration and detailed morphology. This can occur on a local and a global level. When cationic amphipathic peptides such as magainin were studied by biophysical approaches they are found intercalated at the membrane interface where they cause membrane thinning and ultimately lysis. Interestingly, mixtures of peptides such as magainin 2 and PGLa which occur naturally as a cocktail in the frog skin exhibit synergistic enhancement of antimicrobial activities when investigated together in antimicrobial assays but also in biophysical experiments with model membranes. Detailed dose-response curves, presented here for the first time, show a cooperative behaviour for the individual peptides which is much increased when PGLa and magainin are added as equimolar mixture. This has important consequences for their bacterial killing activities and resistance development. In membranes that carry unsaturations both peptides align parallel to the membrane surface where they have been shown to arrange into mesophases involving the peptides and the lipids. This supramolecular structuration comes along with much-increased membrane affinities for the peptide mixture. Because this synergism is most pronounced in membranes representing the bacterial lipid composition it can potentially be used to increase the therapeutic window of pharmaceutical formulations.